PENGARUH KEPEMIMPINAN, MOTIVASI, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi pada PT Astra Honda Motor Gajah Mada Semarang) - Riza Nanda Ariyanto, 14.05.51.0047; Muhaimin, Muhaimin (Students' Journal of Economic and Management, 2018)
This study aims to examine and analyze the influence of leadership, motivation and compensation of the employee performance in the PT. Astra Honda Motor Gajah Mada Semarang. Respondents from the study consist of 98 people in the PT. Astra Honda Motor Gajah Mada Semarang. Model analysis the data used test validity by product moment, reliability test with cronbach alpha and analysis linear regression multiple as using software JBM SPSS version 20,0 to examine and prove a hypothesis research. The data collected after conducted testing the results all data expressed valid and reliable. The result of analysis and discussion shown that: ( 1 ) leadership have a positive and significant effect on of employee performance, ( 2 ) motivation have a positive and significant effect on of employee performance, and ( 3 ) compensation have a positive and significant effect on of employee performance. Keyword : Leadership, Motivation, Compensation, Employees performance